Akuntansi Pada Surau Zam Zam Berdasarkan Isak 35 - Nino Sri Purnama Yanti; Deby Tasya Arinjeni; Fitria Rahmi; Reni Dahar (Jurnal Penelitian Dan Pengkajian Ilmiah Sosial Budaya, 2022)
According to the Interpretation of Financial Accounting Standards (ISAK) 35 financial reporting of non-profit companies consist of statements of financial position, statements of comprehensive income, reports of changes in net assets, statements of cash flows and notes to financial statements. This study aims to look at the Accounting at Surau Zam-Zam based on ISAK 35 concerning Presentation of Financial Statements to Non-profit Oriented Entities. The results of the research on the presentation of financial statements in this surau have not been prepared based on ISAK 35, which must be presented in five forms of financial statements, including statements of financial position, statements of comprehensive income, reports of changes in net assets, statements of cash flows and notes to financial statements. The financial statements of Surau Zam-Zam only include simple financial reports, namely income and expenses without being grouped by account and still using their own language. Therefore, Surau Zam-Zam needs to apply accounting standards for non-profit organizations based on ISAK 35 in the preparation and presentation of its financial statements. This is intended so that the surrounding community believes that the allocation of funds and the accountability of the community's funds at this surau have been managed properly.